2017
DOI: 10.1097/ta.0000000000001473
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guideline adherence during Operation Inherent Resolve

Abstract: Epidemiologic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…Of the publications classified as operational use (n = 61, 42%), 51 publications [ 16 66 ] investigated whether program participation or implementation of an intervention was associated with improved quality of care as measured by a composite indicator. In 10 publications [ 67 76 ] the primary aim was to measure hospital performance and/or changes in performance over time ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the publications classified as operational use (n = 61, 42%), 51 publications [ 16 66 ] investigated whether program participation or implementation of an intervention was associated with improved quality of care as measured by a composite indicator. In 10 publications [ 67 76 ] the primary aim was to measure hospital performance and/or changes in performance over time ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this high crystalloid use, a gradual decrease in mean volumes transfused was reported as a result of changes in crystalloid transfusion paradigms. The unexplained preference of crystalloid based resuscitation over resuscitation using blood products was also by Plackett et al 29 in a series of 114 trauma patients who were treated in a role 2 facility. Of 108 patients who required volume resuscitation, crystalloids were the initial fluid of choice in 76%, despite guidelines instructing the use of blood products as the initial resuscitation fluid.…”
Section: Crystalloid Transfusionmentioning
confidence: 87%
“…A survey from academic hospitals showed that 60% of respondents have a single protocol for all patients. 28 Compliance with a single MHP is poor in published studies, 12,16,29 which raises the concern that consistent care would be further compromised by multiple protocols for different bleeding scenarios. The panel recommended a single, standardized protocol in response to the massively bleeding patient with options to tailor the protocol for specific patient populations.…”
Section: A Single Protocol For All Patientsmentioning
confidence: 99%